The Macroeconomics of Labor and Credit Market Imperfections - Etienne Wasmer; Philippe Weil (Institute for the Study of Labor (IZA), 2000)
Labor market frictions are not the only possible factor responsible for high unemployment. Credit market imperfections, driven by microeconomic frictions and impacted upon by macroeconomic factors such as monetary policy, could also be to blame. This paper shows that labor and credit market imperfections interact in a complementary way - which may explain why European and US unemployment differ so much when labor markets have become more similar at the margin in Europe and the US. To develop this idea, we build a search model that treats credit and labor market imperfections in a symmetrical way. We introduce specificity in credit relationships, and assume that credit to potential entrepreneurs is rationed due to endogenous search frictions, in the spirit of Diamond (1990). These imperfections mirror the job search frictions that we introduce, – la Mortensen- Pissarides (1994), in the labor market.
Keywords: E51; J64; G24; 330; Credit and search frictions; unemployment; monetary policy; Arbeitslosigkeit; Kreditmarkt; Kreditrationierung; Suchtheorie; Arbeitsmarkttheorie; Arbeitsuche; Informationskosten; Makroökonomischer Einfluß; Schätzung; Theorie; OECD-Staaten